Immunomodulation—a general review of the current state-of-the-art and new therapeutic strategies for targeting the immune system - Strzelec, Martyna; Detka, Jan; Mieszczak, Patrycja; Sobocińska, Małgorzata Katarzyna; Majka, Marcin (Frontiers in Immunology, 2023)
In recent years, there has been a tremendous development of biotechnological, pharmacological, and medical techniques which can be implemented in the functional modulation of the immune system components. Immunomodulation has attracted much attention because it offers direct applications in both basic research and clinical therapy. Modulation of a non-adequate, amplified immune response enables to attenuate the clinical course of a disease and restore homeostasis. The potential targets to modulate immunity are as multiple as the components of the immune system, thus creating various possibilities for intervention. However, immunomodulation faces new challenges to design safer and more efficacious therapeutic compounds. This review offers a cross-sectional picture of the currently used and newest pharmacological interventions, genomic editing, and tools for regenerative medicine involving immunomodulation. We reviewed currently available experimental and clinical evidence to prove the efficiency, safety, and feasibility of immunomodulation in vitro and in vivo. We also reviewed the advantages and limitations of the described techniques. Despite its limitations, immunomodulation is considered as therapy itself or as an adjunct with promising results and developing potential.